At Westonci.ca, we connect you with experts who provide detailed answers to your most pressing questions. Start exploring now! Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.

Consider the equation below:

[tex]\[
-2(bx - 5) = 16
\][/tex]

The value of [tex]\( x \)[/tex] in terms of [tex]\( b \)[/tex] is [tex]\( \boxed{} \)[/tex]

The value of [tex]\( x \)[/tex] when [tex]\( b \)[/tex] is 3 is [tex]\( \boxed{} \)[/tex]


Sagot :

Certainly! Let's solve the equation step-by-step.

Consider the equation:
[tex]\[ -2(bx - 5) = 16 \][/tex]

### Solving for [tex]\(x\)[/tex] in terms of [tex]\(b\)[/tex]:

1. Distribute -2 on the left side:
[tex]\[ -2 \cdot (bx) + (-2) \cdot (-5) = -2bx + 10 \][/tex]

2. Substitute and equate it to 16:
[tex]\[ -2bx + 10 = 16 \][/tex]

3. Isolate the term with [tex]\(x\)[/tex] by subtracting 10 from both sides:
[tex]\[ -2bx + 10 - 10 = 16 - 10 \][/tex]
[tex]\[ -2bx = 6 \][/tex]

4. Solve for [tex]\(x\)[/tex] by dividing both sides by [tex]\(-2b\)[/tex]:
[tex]\[ x = \frac{6}{-2b} \][/tex]
Simplify the fraction:
[tex]\[ x = \frac{6}{-2b} = \frac{6}{-2} \cdot \frac{1}{b} = -3 \cdot \frac{1}{b} = -\frac{3}{b} \][/tex]

Thus, the value of [tex]\(x\)[/tex] in terms of [tex]\(b\)[/tex] is [tex]\(-\frac{3}{b}\)[/tex].

### Solving for [tex]\(x\)[/tex] when [tex]\(b\)[/tex] is 3:

1. Substitute [tex]\(b = 3\)[/tex] into the equation [tex]\( x = -\frac{3}{b} \)[/tex]:
[tex]\[ x = -\frac{3}{3} \][/tex]

2. Simplify:
[tex]\[ x = -1 \][/tex]

Thus, the value of [tex]\(x\)[/tex] when [tex]\(b\)[/tex] is 3 is [tex]\(-1\)[/tex].

So, the final answers are:
- The value of [tex]\(x\)[/tex] in terms of [tex]\(b\)[/tex] is [tex]\(-\frac{3}{b}\)[/tex]
- The value of [tex]\(x\)[/tex] when [tex]\(b\)[/tex] is 3 is [tex]\(-1\)[/tex]